2019
DOI: 10.1039/c9ra07821e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic investigation of photocatalytic degradation of organic dyes by a novel zinc coordination polymer

Abstract: Mechanistic presentation of the photocatalytic degradation of organic dye molecules by absorbing UV-vis light energy that spans the florescent compound TIPA's HOMO to LUMO band gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…[7][8][9][10] Many zinc(II) complexes are shown to have the ability to degrade organic dyes in aqueous solution. [11][12][13] To show strong uorescence is a typical behaviour of any zinc(II) complex, and the uorescence intensity usually decreases in presence of different nitroaromatic compounds. [14][15][16][17] So, many zinc(II) complexes have been used for the detection of nitroaromatic explosives by turn off uorescence response.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Many zinc(II) complexes are shown to have the ability to degrade organic dyes in aqueous solution. [11][12][13] To show strong uorescence is a typical behaviour of any zinc(II) complex, and the uorescence intensity usually decreases in presence of different nitroaromatic compounds. [14][15][16][17] So, many zinc(II) complexes have been used for the detection of nitroaromatic explosives by turn off uorescence response.…”
Section: Introductionmentioning
confidence: 99%
“…This ZnCP was combined with a solution containing 1.8 mM concentrations of various scavengers, namely benzoic acid (BA), a scavenger for OH radicals, potassium iodide (KI) for e À , benzoquinone (BQ) for O 2 À radicals, and ammonium oxalate (AO) for hole (h + ). 44,45 The outcomes presented in Fig. 6(a) revealed that the most significant reduction in the photocatalytic rate was achieved by using BQ (67%) followed by KI (86.57%) compared to the 99.52% degradation observed in the blank (absence of scavenger).…”
Section: Trapping Experiments and Degradation Mechanismmentioning
confidence: 97%
“…Diffusion of cOH* species away from the surfaces allows the formation of free cOH radicals, which are important components in the removal of organic pollutants. 40,41 In the mechanism, e − and h + have a major role to play. The involvement of radicals (ROS) is also supported by the scavenging experiment (Section 3.5).…”
Section: Mechanismmentioning
confidence: 99%